Comparative analysis of the energy cost during front crawl swimming in children and adults - Ratel, S.; Poujade, B. (European Journal of Applied Physiology, 2009)
The aim of this study was to investigate the effects of age and gender on the energy cost of front-crawl swimming (Cs). Thirty well-trained swimmers (10 boys, 5 girls, 10 men and 5 women) volunteered to perform a 200 m front-crawl test at a standardized velocity (V). Body length (BL), body mass (BM) and body surface area (BSA) were measured. Oxygen consumption (VO2) was measured using the Douglas bag method and the Cs was calculated as the ratio VO2/V. BM, BL, and BSA were identified as good predictors of Cs. By using allometric modeling, common body size exponents for BM, BL, and BSA were 0.40, 1.30, and 0.61, respectively. When scaling for BM, BM0.40, BL, BL1.30, BSA, and BSA0.61, the Cs was not significantly different among the different swimmers groups. In conclusion, in well-trained swimmers, the size-scaled cost of swimming is not dependent on age and gender.